An Algorithm Based on Wavelet Neural Network for Garment Size Selection - Luo Ronglei; He Wenjie; Li Chengyi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Size fitting problem is a main obstacle to large scale online garment sales.It is the difficult to customers to find the fit garments when they couldn’t try on. In this paper, we present an algorithm base on wavelet neural network to help customer choosing their clothing specifications automatically. After the reasonable wavelet function is selected, we established the model structure and the initial parameters. The wavelet neural network is trained by the body measures and the result of AHP algorithm after normalization. The new data are used to test the network. As a result, the error from wavelet neural network is smaller, and the prediction accuracy is proved than that from the algorithm based on traditional BP network.